Performance evaluation of swimmers: scientific tools - Smith, D. J.; Norris, S. R.; Hogg, J. M. (Sports Medicine, 2002)
The purpose of this article is to provide a critical commentary of the physiological and psychological tools used in the evaluation of swimmers. The first-level evaluation should be the competitive performance itself, since it is at this juncture that all elements interplay and provide the 'highest form' of assessment. Competition video analysis of major swimming events has progressed to the point where it has become an indispensable tool for coaches, athletes, sport scientists, equipment manufacturers, and even the media. The breakdown of each swimming performance at the individual level to its constituent parts allows for comparison with the predicted or sought after execution, as well as allowing for comparison with identified world competition levels. The use of other 'on-going' monitoring protocols to evaluate training efficacy typically involves criterion 'effort' swims and specific training sets where certain aspects are scrutinised in depth. Physiological parameters that are often examined alongside swimming speed and technical aspects include oxygen uptake, heart rate, blood lactate concentration, blood lactate accumulation and clearance rates. Simple and more complex procedures are available for in-training examination of technical issues. Strength and power may be quantified via several modalities although, typically, tethered swimming and dry-land isokinetic devices are used. The availability of a 'swimming flume' does afford coaches and sport scientists a higher degree of flexibility in the type of monitoring and evaluation that can be undertaken. There is convincing evidence that athletes can be distinguished on the basis of their psychological skills and emotional competencies and that these differences become further accentuated as the athlete improves. No matter what test format is used (physiological, biomechanical or psychological), similar criteria of validity must be ensured so that the test provides useful and associative information concerning current or future performance. The practical worth of any proposed testing or monitoring protocol should be carefully evaluated. In addition, the developmental stage of the athlete(s) in question should be reflected in the testing/monitoring programme. Finally, increasing technological innovations will bring to the pool deck or dry-land training area simple, fast and advanced diagnostic tools, particularly in the areas of blood-borne markers of training response and neuromuscular excitability.